Features of interaction of children with developmental disorders with peers and adults - АKHMETZYANOVAANNA I.; ARTEMYEVA, TATIANA V. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The ability of children to interact with their peers and adults allows them to adapt to new social conditions. The aimed of this study was to explain how preschoolers with developmental disorders understand the rules in a normative situation. The research involved 227 children of 5-7 years of age: 95 children with no developmental disorders and 132 children with speech, motor, sensory, and emotional disorders. It was used the technique called "The methodology for the study of preschooler compliance with the rules in a regulatory situation." It is suggested that children of all gnoseological groups